Strategi Pembelajaran Berbasis Masalah dalam Meningkatkan Kemampuan Berpikir Kritis Peserta Didik - Annidaul Husna; Novira Ilmi; Gusmaneli Gusmaneli (Lembag, 2025)
Problem-based learning (PBL) is a student-centered instructional strategy that begins with authentic problems as the starting point for learning. This approach encourages students to actively identify, analyze, and solve problems through a systematic and collaborative scientific thinking process. By integrating real-life situations relevant to students’ experiences, PBL not only enhances critical thinking skills but also develops problem-solving abilities, communication, and teamwork. The implementation of problem-based learning among secondary school students demonstrates a significant improvement in critical thinking compared to conventional, more passive teaching methods. Furthermore, this learning strategy fosters independent and creative learning attitudes and helps students connect theoretical knowledge with practical applications in their environment. Therefore, problem-based learning serves as an effective approach to prepare students for the complex and rapidly changing challenges of the 21st century.